Frequency-Specific Synchronization in the Bilateral Subthalamic Nuclei Depending on Voluntary Muscle Contraction and Relaxation in Patients with Parkinson’s Disease - Kato, Kenji; Yokochi, Fusako; Iwamuro, Hirokazu; Kawasaki, Takashi; Hamada, Kohichi; Isoo, Ayako; Kimura, Katsuo; Okiyama, Ryoichi; Taniguchi, Makoto; Ushiba, Junichi (Frontiers in Human Neuroscience, 2016)
The volitional control of muscle contraction and relaxation is a fundamental component of human motor activity, but how the processing of the subcortical networks, including the subthalamic nucleus (STN), is involved in voluntary muscle contraction (VMC) and voluntary muscle relaxation (VMR) remains unclear. In this study, local field potentials (LFPs) of bilateral STNs were recorded in patients with Parkinson’s disease (PD) while performing externally paced VMC and VMR tasks of the unilateral wrist extensor muscle. The VMC- or VMR-related oscillatory activities and their functional couplings were investigated over the theta (4–7 Hz), alpha (8–13 Hz), beta (14–35 Hz), and gamma (40–100 Hz) frequency bands. Alpha and beta desynchronizations were observed in bilateral STNs at the onset of both VMC and VMR tasks. On the other hand, theta and gamma synchronizations were prominent in bilateral STNs specifically at the onset of the VMC task. In particular, just after VMC, theta functional coupling between the bilateral STNs increased, and the theta phase became coupled to the gamma amplitude within the contralateral STN in a phase-amplitude cross-frequency coupled manner. On the other hand, the prominent beta-gamma cross-frequency couplings observed in the bilateral STNs at rest were reduced by the VMC and VMR tasks. These results suggest that STNs are bilaterally involved in the different performances of muscle contraction and relaxation through the theta-gamma and beta-gamma networks between bilateral STNs in patients with PD.